2006
DOI: 10.1209/epl/i2005-10375-8
|View full text |Cite
|
Sign up to set email alerts
|

Spin-lattice relaxation phenomena in manganite La 0.7 Sr 0.3 MnO 3 thin films

Abstract: 2Time-resolved magneto-optics was used to study spin-lattice relaxation dynamics in thin epitaxial La 0.7 Sr 0.3 MnO 3 films. Two distinct recovery regimes of the ferromagnetic order can be resolved upon photoexcitation, which manifest themselves by two different relaxation times. A pump pulse energy independent spin-lattice relaxation time can be deduced. Due to a weak spin-orbit coupling in manganites this spin-lattice relaxation time is much longer than in ferromagnetic metals. Heat flow into the substrate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The remagnetization curve after the maximal demagnetization was fitted for t < 10 ps with an exponential function. The exponential fitting with for the initial remagnetization is used widely 40 , 41 , where A 0 is approximately proportional to ( T s max −T eq ) and τ eff is an effective relaxation time. In particular, it was reported that τ eff may be a direct measure of an effective characteristic time of the lattice–spin interaction 40 43 .…”
Section: Resultsmentioning
confidence: 99%
“…The remagnetization curve after the maximal demagnetization was fitted for t < 10 ps with an exponential function. The exponential fitting with for the initial remagnetization is used widely 40 , 41 , where A 0 is approximately proportional to ( T s max −T eq ) and τ eff is an effective relaxation time. In particular, it was reported that τ eff may be a direct measure of an effective characteristic time of the lattice–spin interaction 40 43 .…”
Section: Resultsmentioning
confidence: 99%
“…This lead us to an investigation of electron-lattice coupling. Since the effective relaxation time of the MOKE signal is known to be closely related to the coupling strength between electrons and lattices 18 19 , time–resolved MOKE measurements were carefully performed to study the dynamic behavior of electron /lattice coupling in Co/Pt multilayers. The time-resolved MOKE signals are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…33, with the thermal conductivity k th Ϸ 4.7 W m −1 K −1 , see Ref. 34. The currents measured in the initial resistance state typically do not exceed 10 pA under applications of several volts, corresponding to a negligible temperature rise of ⌬T Յ 0.01 K. However, after switching to LRS the current values suddenly increase by several orders of magnitude.…”
Section: Appendix B: Estimation Of Contact Radius Joule Heating Andmentioning
confidence: 98%